Decline in on-demand fishing gear costs with learning - Alkire, Carolyn (Frontiers in Marine Science, 2022)
Gear entanglement and vessel collisions are the major known causes of injuries to the critically endangered North Atlantic right whale (Eubalaena glacialis) and other marine animals. Whale entanglements often occur in endlines (the fixed vertical lines between fishing traps and surface buoys) and removal of these lines in “on-demand” or “ropeless” fishing gear has been presented as a potential solution. These fishing systems use acoustic and timed releases to locate and retrieve a submerged trap, endline, and buoy (or lift bag or spool) to the surface. On-demand fishing gear commercially in use costs up to $8,000 for a deck unit and up to $4,000 per acoustic release. Developers expect on-demand fishing component costs to drop as production ramps up. The correlation between production cost or labor hours per unit and cumulative production have been described as ‘experience curves’ or ‘learning curves.’ The learning model is the most common approach to projecting production costs in electronics and other high-tech industries, with the log-linear model based on the Wright learning curve the most frequently used modelling approach. Wright’s equation is used to calculate on-demand fishing gear costs for northeastern U.S. commercial fishing vessels operating in federal lobster management areas. These vessels represent approximately 70% of entanglement risk, estimated by the National Marine Fisheries Service. The use of on-demand gear would therefore initially be most effective in reducing the risk of whale entanglement (and mortality) in commercial fishing areas in these waters. It is estimated that the cost of on-demand gear for the 1,494 vessels operating in federal waters would total $58.1 million, with an average of $38,899 per vessel if releases were used on all endlines. If vessels fishing 5 or more traps per trawl use a release on 1 endlines per trawl, the total cost is estimated at $38.2 million, with an average of $25,552 per vessel. The initial cost of on-demand fishing gear may be an obstacle to widespread adoption. Funding and loan programs are available and there is precedent for government and community assistance to workers in industries affected by resource management regulations.